1990
DOI: 10.1016/0014-5793(90)80535-q
|View full text |Cite
|
Sign up to set email alerts
|

A semi‐empirical method for prediction of antigenic determinants on protein antigens

Abstract: Analysis of data from experimeotally determined antigenic sites on proteins has revealed that the hydrophobic residues Cys, Z_XU and Val, if they occur on the surface of a protein, are more likely to be a part of antigenic sites. A semi-empirical method which makes use of physicochemical properties of amino acid residues and their frequencies of occurrence in expe~ment~ly known segmental epitopes was developed to predict antigenic determinants on proteins. Application of this method to a large number of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
1,020
0
7

Year Published

1995
1995
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,277 publications
(1,031 citation statements)
references
References 9 publications
4
1,020
0
7
Order By: Relevance
“…The antigenic domains of goat and all 12 animal species were predicted by (Kolaskar & Tongaonkar, 1990) method using online software tool (http://imed.med.ucm.es/tool/antigenic.pl). The results revealed that 11 antigenic domains of IL‐33 from goat lie from 4th to 225th amino acids (Figure 4) and 143 antigenic domains for 12 animal species including goat lie from 4th to 3114th amino acids (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…The antigenic domains of goat and all 12 animal species were predicted by (Kolaskar & Tongaonkar, 1990) method using online software tool (http://imed.med.ucm.es/tool/antigenic.pl). The results revealed that 11 antigenic domains of IL‐33 from goat lie from 4th to 225th amino acids (Figure 4) and 143 antigenic domains for 12 animal species including goat lie from 4th to 3114th amino acids (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Linear B cell epitopes: Linear epitope constitutes a single continuous stretch of amino acids within a protein sequence antigen recognized by soluble or membrane bound antibodies (Vivona et al 2008). Among the algorithms used for linear B cell epitope prediction, ABCPred is based on artificial neural networks and BcePred uses physico-chemical properties for epitope prediction (Kolaskar and Tongaonkar 1990;Raghava 2006a, b, 2007 (Zhang et al 2008;Bui et al 2005;Wang et al 2010;Moutaftsi et al 2006;Parker et al 1994;Lundegaard et al 2008). 4.…”
Section: Immunoinformaticsmentioning
confidence: 99%
“…The amino acid sequence heterogeneity at each residue position is indicated in the red regions in Figure 1 (higher peaks indicate greater sequence diversity). The antigenicity of the sequences, which was calculated using the algorithm of Kolaskar and Tongaonkar, 52 is indicated by the black lines (higher peaks, either above or below the midline indicate greater antigenicity). Many of the regions of high antigenicity (black lines) also show highly variable amino acid sequences (red regions), suggesting the possibility of strain-to-strain variation in antigenicity.…”
Section: Why Are There Disparities In the Published Reports Of Test Pmentioning
confidence: 99%